ISLAMISM IN DAYAH: SHAFI'IYAH, HANBALIYAH, AND POPULAR ISLAM - Sofanudin, Aji; Ibda, Hamidulloh; Syafi’, Moh.; Fikri, Mumtazul; Marzuki, Marzuki; Tsauro, Ahalla (Islam Futura, 2023)
Islamism is a set of ideologies that believe that religion and the state are one (addinu waddaulah) as happened in Aceh, Indonesia. This research aims to find out the variants of Islamism in integrated dayah in Aceh. The phenomenological method was used to reveal the phenomenon of Islamism in six integrated dayah. The findings show that there are three variants of Islamism in integrated dayah in Aceh, namely shafiyah style, hanbaliyah style and Islamic popular style. This research is limited to integrated dayahs and only reveals dayah variants. Further research is needed on Islamist networks in various types of dayah in Aceh.